The Effectiveness of Clean and Healthy Lifestyle Behavior Education in Preventing Scabies among Children at the Medan Juvenile Correctional Institution - Lubis, Anisa Taqwa; Ginting, Chrismis Novalinda; Nasution, Sri Wahyuni (Riviera Publishing, 2026)
Scabies is a contagious skin disease that remains a public health problem, particularly among children living in communal settings with high population density, such as Juvenile Correctional Institutions (Lembaga Pembinaan Khusus Anak/LPKA). Clean and Healthy Living Behavior (Perilaku Hidup Bersih dan Sehat/PHBS) plays an important role in preventing the transmission of scabies through changes in individual behavior. This study aimed to analyze the effectiveness of a community health promotive intervention through PHBS education in preventing scabies among children at LPKA Class I Medan. This study employed a quasi-experimental design with a pre-test and post-test group design. The research sample consisted of all 125 children residing at LPKA Class I Medan, selected using total sampling technique. The intervention comprised PHBS education delivered using PowerPoint presentation media. Data were collected before and after the intervention using a structured questionnaire assessing knowledge, attitudes, and practices related to PHBS for scabies prevention. Data analysis was performed using univariate and bivariate analyses, with the Wilcoxon Signed Rank Test applied due to non-normal data distribution. The results showed a significant increase in respondents’ knowledge and attitudes following the PHBS educational intervention (p < 0.001), as well as a significant improvement in scabies prevention practices (p = 0.010). The greatest improvement was observed in the knowledge aspect, while changes in practice were relatively lower, possibly influenced by limitations in facilities and environmental conditions within the LPKA.